Clinical and Microbiological Characteristics of Intestinal Microbiocenosis Disorders In HIV-Positive Children with Acute Diarrhea - Muminova Makhbuba Teshaevna (International Journal of Medical Science and Public Health Research, 2026)
Acute infectious diarrhea (AID) is a frequent and serious complication in children living with HIV. This study aims to investigate the composition and severity of intestinal microbiota disruption (dysbiosis) in HIV-positive children with AID compared to HIV-negative peers. A total of 499 children aged 7–18 years were included. Dysbiosis was classified into four stages, and correlations with clinical parameters, immunodeficiency levels, and viral loads were assessed. Our results show that advanced dysbiosis (stages III–IV) is significantly more prevalent in HIV-infected children, particularly those with high viral loads and severe immunodeficiency. Early detection and correction of dysbiosis are essential to prevent further complications and support immune recovery.